The State of the African American Male - Zamani-Gallaher, Eboni M.; Polite, Vernon C. (Michigan State University Press, 2012)
The circumstances affecting many African American males in schools and society remain complex and problematic. In spite of modest gains in school achievement and graduation rates, conditions that impede the progress of African American males persist: high rates of school violence and suspensions, overrepresentation in special education classes, poor access to higher education, high incidence of crime and incarceration, gender and masculine identity issues, and HIV/AIDS and other health crises. The essays gathered here focus on these issues as they exist for males in grades K-12 and postsecondary education in Michigan. However, the authors intend their analyses and policy recommendations to apply to African American males nationally. Although it recognizes the current difficulties of this population overall, this is an optimistic volume, with a goal of creating policies and norms that help African American males achieve their educational and social potential. In this era of widespread change for all members of American society-regardless of race-this book is a must-read for educators and policymakers alike.